High-Resolution Axonal Bundle (Fascicle) Assessment and Triple-Echo Steady-State T2 Mapping of the Median Nerve at 7 T: Preliminary Experience. Issue 8 (August 2016) - Riegler, Georg; Drlicek, Gregor; Kronnerwetter, Claudia; Heule, Rahel; Bieri, Oliver; Bodner, Gerd; Lieba-Samal, Doris; Trattnig, Siegfried
Abstract : Objectives: The aims of this preliminary study were to determine the number of axonal bundles (fascicles) in the median nerve, 1 using a high-resolution, proton density (PD)–turbo spin echo (TSE) fat suppression sequence, and to determine normative T2 values, measured by triple-echo steady state, of the median nerve in healthy volunteers and in patients with idiopathic carpal tunnel syndrome (CTS), at 7 T. 2 Materials and Methods: This prospective study was approved by the local ethics committee and conducted between March 2014 and January 2015. All study participants gave written informed consent. Six healthy volunteers (30 ± 12 years) and 5 patients with CTS (44 ± 16 years) were included. Measurements were performed on both wrists in all volunteers and on the affected wrist in patients (3 right, 2 left). Based on 5-point scales, 2 readers assessed image quality (1, very poor; 5, very good) and the presence of artifacts that might have a possible influence on fascicle determination (1, severe artifacts; 5, no artifacts) and counted the number of fascicles independently on the PD-TSE sequences. Furthermore, T2 values by region of interest analysis were assessed. Student t tests, a hierarchic linear model, and intraclass correlation coefficients (ICCs) were used for statistical analysis. Results: Proton density-TSE image quality and artifacts revealed a median of 5 in healthy volunteers and 4 in patients with CTS for both readers. Fascicle count of the median nerve ranged from 13 to 23 in all subjects, with an ICC of 0.87 (95% confidence interval [CI], 0.67–0.95). T2 values were significantly higher ( P = 0.023) in patients (24.27 ± 0.97 milliseconds [95% CI, 22.19–26.38]) compared with healthy volunteers (21.01 ± 0.65 milliseconds [95% CI, 19.61–22.41]). The ICC for all T2 values was 0.97 (95% CI, 0.96–0.98). Conclusions: This study shows the possibility of fascicle determination of the median nerve in healthy volunteers and patients with CTS (although probably less accurately) with high-resolution 7 T magnetic resonance imaging, as well as significantly higher T2 values in patients with CTS, which seems to be associated with pathophysiological nerve changes.